Seaweed lipids as nutraceuticals - Mišurcová, Ladislava; Ambrožová, Jarmila; Samek, Dušan (Advances in food and nutrition research, 2011)
Seaweeds are known as low-energy food. Despite low lipid content, ω-3 and ω-6 polyunsaturated fatty acids (PUFAs) introduce a significant part of seaweed lipids. PUFAs are the important components of all cell membranes and precursors of eicosanoids that are essential bioregulators of many cellular processes. PUFAs effectively reduce the risk of cardiovascular diseases, cancer, ostheoporosis, and diabetes. Because of the frequent usage of seaweeds in Asia and their increasing utilization as food also in other parts of the world, seaweeds could contribute to the improvement of a low level of ω-3 PUFAs, especially in the Western diet. The major commercial sources of ω-3 PUFAs are fish, but their wide usage as food additives is limited for the typical fishy smell, unpleasant taste, and oxidative nonstability. Nevertheless, growing requirements of healthy functional foods have led to produce PUFAs as nutraceuticals in controlled batch culture of marine microalgae, especially Thraustochytrium and Schizochytrium strains.
Keywords: Seaweed; potravní doplňky; fyziologie výživy; mořské řasy; Dietary Supplements; kyseliny mastné omega-6; omega-3 mastné kyseliny; lidé; Fatty Acids, Omega-3; Humans; Nutritional Physiological Phenomena; Fatty Acids, Omega-6